QOL-17. BIOLOGICAL CORRELATES OF QUALITY OF SURVIVAL AND NEUROCOGNITIVE OUTCOMES IN MEDULLOBLASTOMA; A META-ANALYSIS OF THE SIOP-UKCCSG-PNET3 AND HIT-SIOP-PNET4 TRIALS. (4th December 2020) - Chevignard, Mathilde; Bull, Kim; Holt, James; Heng, Marie-Amelie; Kennedy, Colin; Doz, Francois; Lannering, Birgitta; Rutkowski, Stefan; Massimino, Maura; Clifford, Steven; Hicks, Debbie
Abstract: Relationships between biological factors (genetic, tumour molecular subgroup) and neurocognitive/Quality of Survival (QoS) outcomes in medulloblastoma survivors are emerging, based on studies of limited retrospective cohorts. Integrated investigations of the medulloblastoma late-effects pathway (considering biological, clinical and treatment factors), using larger clinically-controlled cohorts, are now essential to determine their independent significance and potential for clinical application. In a combined cohort of SIOP-UKCCSG-PNET3 and HIT-SIOP-PNET4 patients (n=150), molecular subgroup (MBWNT, MBSHH, MBGrp3, MBGrp4 ) was assessed against QoS measures [health status: HUI3; emotional and behavioural difficulties: SDQ; Health-related Quality of Life (HrQoL): PedsQL]. Additionally, in DNA remaining from HIT-SIOP-PNET4 (n=74), 39 candidate SNPs (involved in metabolism, DNA maintenance/repair, neural growth/repair and oxidative stress/inflammation) were genotyped by multiplexed MALDI-TOF MassArray and assessed against Wechsler Intelligence Scale (WISC) scores. Molecular subgroup was significantly associated with HrQoL and health status in univariate analyses; MBGrp4 predicted significantly worse outcomes than MBSHH and MBGrp3 (p<0.05), but not in multivariate analyses taking into consideration other significant and reported QoS predictors (e.g. treatment, gender, age). In contrast, 6 SNPs were significantly associated with ≥1 WISC domain; 4/6 showed associations across domains. 3 SNPs were independently prognostic in multivariate analyses, and further significant associations were apparent at the gene ( BDNF, APOE ) and pathway (folate) level. This cross-discipline, international study encompassing two medulloblastoma trials has identified relationships between molecular subgroup, genotype and survivorship outcomes. These findings now require assessment in larger series, to inform our understanding of medulloblastoma survivorship outcomes and impact future disease management strategies.